Impact of virtual group-based acceptance and commitment therapy on social adjustment and work-family conflict among intern nurses: a randomized control trial - El-Ashry, Ayman Mohamed; Elhay, Eman Sameh Abd; Taha, Samah Mohamed; Salem, El Saied Abd El Hamid El Sayed; El-Sayed, Mona Metwally (BMC psychiatry, 2023)
Background An action-oriented approach such as acceptance and commitment therapy may help reduce the fusion of conflicting ideas, empower new intern nurses to act according to their values, and maximize their psychological flexibility. Objective To evaluate the impact of a virtual group-based acceptance and commitment therapy intervention on intern nurses’ social adjustment and work-family conflict. Design A parallel, single-blind randomized control trial on intern nurses ( n = 70) was randomly allocated to either a six-session online acceptance or commitment therapy intervention ( n = 35) or a waiting list control group ( n = 35), with each session lasting 90 min. Measures The work-related acceptance and action questionnaire, the social adjustment scale-self report, and the work-family conflict scale before, after, and one month after the intervention. Results The psychological flexibility mean score of the study group was significantly higher than that of the control group (43.11 vs. 34.15, p < .001) immediately after the intervention, and this effect was sustained one month after the intervention (41.88 vs. 33.21, p < .001) with a more significant effect size (F = 128.457, p < .001, η2 = 0.791). The social adjustment mean score of the study group had significantly improved in all four subscales, with statistically significant differences ( p < .001). One month after the intervention, the study group had significantly higher scores than the control group in total score, with statistically significant differences ( p < .001) and large effect sizes (η2 = 0.932). Work-family conflict mean score of the study group was decreased immediately after the intervention, with statistically significant differences ( p < .001). One month after the intervention, the study group had significantly lower scores than the control group in all three subscales of the WFCS, with statistically significant differences ( p < .001) and large effect sizes (η2 = 0.943). Conclusion Our findings proved that the virtual group-based ACT intervention effectively improved psychological flexibility and social adjustment, reducing work-family conflict among intern nurses. These findings suggest that the virtual group-based ACT intervention can be a practical approach to improving intern nurses’ mental health and well-being, which could affect their job performance and overall quality of life. Trial registration The study was registered retrospectively as a randomized clinical trial on 10/2/2023, reference number; NCT05721339 .